You Can't Stop the Revolution: Community Disorder and Social Ties in Post-Ferguson America - Boyles, Andrea S. (University of California Press, 2019)
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Introduction -- 1. Between a Rock and a Hard Place -- 2. (Dis)order and Informal Social Ties in the United States -- 3. “A Change Gotta Come”: Informal Integration -- 4. Making Black Lives Matter -- 5. “We Are in a State of Emergency” -- 6. (No) Conclusion and Discussion -- Notes -- References -- Index